A Hunger to Teach: Recruiting Inuit Teachers for Nunavut - Berger, Paul; Inootik, Karen; Jones, Rebecca; Kadjukiv, Jennifer (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2016)
We describe findings from participatory research conducted by a southern-based researcher from Thunder Bay, Ontario, and Nunavut Arctic College’s Teacher Education Program students. Together, they interviewed 128 high school students from 11 communities to determine what attracts Inuit youth to teaching and what might discourage them from becoming teachers. The research was based on the premise that Nunavut’s schools cannot be Inuit schools without many more Inuit teachers. We found that many Inuit youth have considered becoming teachers, but they face barriers to doing so. They expressed concerns about housing, finances, leaving their home communities, and their own academic preparedness. Many lacked information about teacher education programs. We recommend addressing these concerns, in part, by using Nunavut Teacher Education Program students to educate high school students about the program and to encourage them to become teachers.